Influence of Product Innovation on MSME Marketing Performance at the Cooperative and SME Office of South Sulawesi Province - Cudai, Andi; Guntur, Muhammad; Sopia Rukmana, Novayanti; Nur Aina, Asri; Nur Pratiwi Johansyah, Oky (KnE Social Sciences, 2024)
Micro, small, and medium enterprises as a trade sector dominates more than 99% of the Indonesian economy and is capable of becoming a driving force for national and regional development. This study aims to describe the marketing performance of micro, small, and medium enterprises in the trade sector in South Sulawesi. The research is a type of survey research done using a quantitative approach. Survey research explains causal relationships in hypothesis testing, with the intent of: (1) explorative, (2) descriptive, (3) explanation or confirmation, (4) evaluation, (5) prediction, (6) operational research, and (7) development of social indicators. The results of the study describes that the variable performance of marketing of micro enterprises in the trade sector in South Sulawesi is influenced by the product innovation variable. The higher the product innovation carried out by the trade sector of micro, small, and medium enterprises, the higher is the marketing performance. Keywords: product innovation, marketing performance, trade sector MSMEs